TI_GERICHTE 11.2014.75 vom 6. Oktober 2016 , Opere sporgenti sul fondo altrui: vano nel sottotetto dello stabile contiguo - TI Tribunale d'appello (2016)
Opere sporgenti sul fondo altrui: vano nel sottotetto dello stabile contiguo